Recent Advances of 1,3,5-Triazinanes in Aminomethylation and Cycloaddition Reactions - Liang, Dong; Xiao, Wen-Jing; Chen, Jia-Rong (Synthesis, 2020)
1,3,5-Trisubstituted 1,3,5-triazinanes (hexahydro-1,3,5-triazines), as stable and readily available surrogates for formaldimines, have found extensive applications for the construction of various nitrogen-containing compounds. The formaldimines, formed in situ from this reagent class, can participate in various aminomethylation and cycloaddition reactions. This short review presents recent advances in this field with emphasis on the conceptual ideas behind the developed methodologies and the reaction mechanisms.1 Introduction2 Aminomethylations with 1,3,5-Triazinanes3 Cycloadditions with 1,3,5-Triazinanes3.1 Use of 1,3,5-Triazinanes as Two-Atom Synthons3.2 Use of 1,3,5-Triazinanes as Three-Atom Synthons3.3 Use of 1,3,5-Triazinanes as Four-Atom Synthons3.4 Use of 1,3,5-Triazinanes as Six-Atom Synthons4 Conclusions
Keywords: hexahydro-1,3,5-triazines; 1,3,5-triazinanes; formaldimines; aminomethylations; cycloadditions; nitrogen-containing compounds